(untitled) (Progressive Agriculture, 2020)
This study was conducted to evaluate the Kapotaksha River water pollution status and its impacts on Human health and Environment. This study conducted a case study on four selected areas (Barakpur, Srirampur, Prbazar, and Gouranandapur) on the Kapotaksha river bank at Jhikargas Upazila. This river water pollution occurs by some natural process such as flood, storm, and natural biodegraded. But human activities are major reasons for the river water pollution. Industrialization, urbanization, domestic waste, sewage system, agrochemicals, etc are major causes for river water pollution. This more polluted water has an impact on human health and environment. This study was conducted to find out the polluted water due to various types of diseases such as scabies, asthma, dysentery and respiratory disease. Most of the people (49%) are affected by Scabies, 4% are affected by diarrhea, 5% are affected by dysentery, 25% of people are suffering from respiratory diseases and 4% are suffering from asthma and the polluted water pollutes soil by using the water in agriculture purpose answered by 20% respondents which is 100% of farmer respondents. If someone does not use this water can not affect soil answered by 80% of respondents. This river water becomes more polluted and harmful for human health and environment because this water hampered by the local colony, local trader, lack of proper management of sewage system, miss-use on the riverbank area for the dumping various solid waste on the river bank, chemical fertilizers, industries etc. At present now we cannot fulfill control this continuous river water pollution but we can minimize this problem and it would be positive for human health, others living organisms and Environment. Progressive Agriculture 31 (1): 1-9, 2020